AUDIT SISTEM INFORMASI AKUNTANSI SAWITACCT PADA PT. BERKAT SAWIT SUKAMAJU MENGGUNAKAN FRAMEWORK COBIT 2019 DOMAIN DSS - Alfin Alfin; Sharon Jadelyn Villian Johan; Novela Artika Sari Dewi; Mayang Sari (CV. Denasya Smart Publisher, 2026)
PT Berkat Sawit Sukamaju utilizes an accounting information system called SawitACCT to support financial transaction processing and company financial reporting activities. However, several problems were identified, including the absence of user access rights management, unrestricted transaction modification and deletion by users, backup systems using local hard disks, and system disruptions causing data loss. This study aims to evaluate the effectiveness of information system controls using the COBIT 2019 framework, specifically DSS01, DSS04, and DSS05. The research method used is descriptive qualitative through observation, interviews, and documentation. The audit results indicate that DSS01 and DSS05 are at Capability Level 2 (Managed Process), while DSS04 is at Capability Level 1 (Performed Process). The findings show that the company still requires improvements in user access management, backup systems, antivirus maintenance, and server infrastructure optimization. This study concludes that improvement of information system governance is necessary to support operational continuity and information security within the company.